Living with strangers : the nineteenth-century Sioux and the Canadian-American borderlands - McCrady, David G. (University of Nebraska Press, 2006)
"The story of the Sioux who moved into the Canadian-American borderlands in the later years of the nineteenth century is told in its entirety for the first time here. Previous histories have been divided by national boundaries and have focused on the famous personages involved, paying scant attention to how Native peoples on both sides of the border reacted to the arrival of the Sioux. Using material from archives across North America, Canadian and American government documents, Lakota winter counts, and oral history, Living with Strangers reveals how the nineteenth-century Sioux were a people of the borderlands."--Jacket